2002
DOI: 10.1161/hs0402.105553
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Recombinant S1179D Endothelial Nitric Oxide Synthase in Canine Cerebral Arteries

Abstract: Background and Purpose-Bovine endothelial nitric oxide synthase (eNOS) is phosphorylated directly by the protein kinase Akt at serine 1179. Mutation of this residue to the negatively charged aspartate (S1179DeNOS) increases nitric oxide (NO) production constitutively in the absence of agonist stimulus. The present study was designed to determine the effect of mutant S1179DeNOS gene expression on vasomotor function of canine cerebral arteries. Methods-Isolated basilar and middle cerebral arteries were exposed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…In a series of previous studies, we demonstrated that intracisternal gene delivery resulted in expression of recombinant protein in adventitial fibroblasts of cerebral arteries (3,12,13,25,36,42). In the present study, successful gene transfer was confirmed by the increased levels of Epo in CSF and by the detection of Epo in the AdEpo-transduced basilar arteries.…”
Section: Discussionsupporting
confidence: 78%
“…In a series of previous studies, we demonstrated that intracisternal gene delivery resulted in expression of recombinant protein in adventitial fibroblasts of cerebral arteries (3,12,13,25,36,42). In the present study, successful gene transfer was confirmed by the increased levels of Epo in CSF and by the detection of Epo in the AdEpo-transduced basilar arteries.…”
Section: Discussionsupporting
confidence: 78%
“…Comparisons with WT mice may be less revealing because the phosphorylation state of the S1179 residue in WT mice cannot be controlled and because the expression levels in the transgenic mice were less than WT eNOS levels. In this regard, reconstitution of eNOS KO mice with low levels of either S1179A or S1179D transgenes may explain why we did not observe compensatory effects of increased transgene expression that have been reported in some (28) but not other (12,27) systems.…”
Section: Figuresupporting
confidence: 49%
“…To date, the effects of S1179A and S1179D mutants have been characterized in cultured cells (12,14,26) and using ex vivo gene transfer into isolated vessels (12,27,28). Both S1179A and S1179D eNOS are enzymatically active, so S1179…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, substitution of aspartate for serine mimics the negative charge imparted by the phosphate and renders eNOS constitutively active by increasing the rate of electron flux through the protein and increases basal NO production severalfold (21). The delivery method and activity of this construct has been well characterized (22)(23)(24). As seen in Fig.…”
Section: Adenoviral Delivery Of Constitutively Active Enos Rescues Limbmentioning
confidence: 99%